2023
DOI: 10.1186/s12879-023-08116-z
|View full text |Cite
|
Sign up to set email alerts
|

Association of TLR4 and TLR9 gene polymorphisms with cervical HR-HPV infection status in Chinese Han population

Abstract: Background Toll-like receptors (TLRs) may be involved in the natural history of human papillomavirus (HPV) infection. In our study, we aimed to investigate the association of TLR4 (rs10116253, rs1927911, rs10759931) and TLR9 (rs187084, rs352140) gene polymorphisms with cervical persistent high-risk HPV (HR-HPV) infection, as well as multiple HR-HPV infections. Methods A total of 269 study subjects were enrolled and grouped by retrospectively analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 46 publications
1
5
0
Order By: Relevance
“…The mutant genotypes of TLR9 rs187084 and rs352140 were associated with persistent and multiple high-risk human papillomavirus infection in Chinese Han population (29). In addition, a significantly higher frequency of the rs187084 C allele was observed in Epstein Barr virus negative infected healthy subjects (30). Patients with TLR9 rs187084 C allele and TC, CC genotype have higher risk for COVID-19 in our study.…”
Section: Accepted Manuscriptsupporting
confidence: 50%
“…The mutant genotypes of TLR9 rs187084 and rs352140 were associated with persistent and multiple high-risk human papillomavirus infection in Chinese Han population (29). In addition, a significantly higher frequency of the rs187084 C allele was observed in Epstein Barr virus negative infected healthy subjects (30). Patients with TLR9 rs187084 C allele and TC, CC genotype have higher risk for COVID-19 in our study.…”
Section: Accepted Manuscriptsupporting
confidence: 50%
“…TLR9 haplotypes and polymorphisms have been previously shown to correlate with potential risk of cervicitis 35 , cervical cancer 71 , as well as susceptibility and the development of symptoms after HR-HPV and C. trachomatis infection 36,72 . TLR9-stimulatory adjuvants have also been used extensively in chlamydial vaccine development 7377 .…”
Section: Discussionmentioning
confidence: 99%
“…Given its origin 69 (and re-emergence 70 ) as a murine lung pathogen, C. muridarum likely evolved under heightened selective pressure in this environment and the reduced stimulatory potential of its gDNA may be evidence of a pathoadaptation to this niche. TLR9 haplotypes and polymorphisms have been previously shown to correlate with potential risk of cervicitis 35 , cervical cancer 71 , as well as susceptibility and the development of symptoms after HR-HPV and C. trachomatis infection 36,72 . TLR9stimulatory adjuvants have also been used extensively in chlamydial vaccine development [73][74][75][76][77] .…”
Section: Discussionmentioning
confidence: 99%
“…For most subjects, HPV-associated lesions are cleared within 1–2 years [ 67 ]. Another study showed that the median HR-HPV clearance time was 10.5 months [ 66 , 67 , 68 , 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of a correlation between TLR9 immune signal and macrophage number, we suppose that other immune determinants may be assessed, such as TLR4, another important PRR involved in the immune response in HPV [ 57 , 68 , 71 ], and DCs, as professional APCs.…”
Section: Discussionmentioning
confidence: 99%